Moderni habsburški popisi prebivalstva v Cislajtaniji in njihove zlorabe v avstrijskoilirskem Primorju iz perspektive ohranjenih popisnih listov (zapisnic in naznanilnic) - Pletikosić, Ivica (Revija za geografijo, 2024)
The statistical literature, which contains data for the period of the Habsburg modern population censuses, was created on the basis of calculations by municipal officials. Only they leafed through the notes and notices and sent the calculated data to Vienna for printing by the state printing house. Re-examining these sources offers a whole new perspective on the censuses in question. The purpose of the article is to present the biggest differences between the established truths and the view from this new angle.
Keywords: 19. st.; 19th cent.; 20. st.; 20th cent.; Austria-Hungary; Austrian-Illyrian Primorje; avstrijsko-ilirsko Primorje; Avstro-Ogrska; popisi prebivalstva; population censuses